(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical characteristics and to determine the prevalence and associated factors of intrauterine growth restriction in very preterm infants at the Neonatal Care and Treatment Center, National Hospital of Obstetrics and Gynecology in 2024. Subjects and methods: This was a prospective, longitudinal descriptive study conducted on 285 very preterm infants (gestational age from 28 to under 32 weeks) who met the inclusion criteria, from June 2024 to April 2025. Data were collected from medical records and clinical follow-up. Statistical analysis was performed using Stata 16 with appropriate statistical tests. Results: The prevalence of intrauterine growth restriction was 13.7%. Birth weight in the intrauterine growth restriction group was significantly lower than in the non-intrauterine growth restriction group (997.4g vs. 1405.9g, p < 0.001). Infants with intrauterine growth restriction required longer duration of parenteral nutrition than the group without intrauterine growth restriction (8.0 days vs. 5.9 days, p = 0.001). There was no significant difference between the two groups in terms of time to initiation of enteral feeding or time to reach 130 ml/kg/day. Conclusion: Intrauterine growth restriction remains a relevant issue in very preterm infants. Low birth weight and prolonged parenteral nutrition are key risk factors. Early monitoring and appropriate nutritional intervention play a crucial role in the care of this high-risk population.